Intrinsic emission and electron-hole trapping centers in Li2SO4-Cu crystals - Nurakhmetov, T; Alibay, T.T.; Zhangylyssov, K.B.; Sadykova, B.M.; Daurenbekov, D.H.; Kainarbay, A.Zh.; Zhunusbekov, A. M.; Yussupbekova, B. N.; Dolomatov, M. Y.; Salikhodzha, Zh. M.; Tolekov, D.A. (Eurasian Journal of Physics and Functional Materials, 2026)
In thepresent work, the emission and excitation spectrain Li2SO4-Cu crystalshave been obtainedby the methods of vacuum-ultraviolet and thermoactivation spectroscopy. We have studied the nature of emission from a pressed and annealed sample of Li2SO4-Cu powders. It has been revealed that at low temperatures Cu0-SO. -centers are formed during the trap of electrons by Cu+ -centers and during 4 localization of SO. 4 -radicals in the form of localized hole centers.Recommended CitationNurakhmetov, T. N.; Salikhodzha, Zh. M.; Dolomatov, M. Y.; Yussupbekova, B. N.; Zhunusbekov, A. M.; Kainarbay, A. Zh.; Daurenbekov, D. H.; Sadykova, B. M.; Zhangylyssov, K. B.; Alibay, T. T.; and Tolekov, D. A. (2021) "Intrinsic emission and electron-hole trapping centers in Li2SO4-Cu crystals," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 2, Article 7.DOI: https://doi.org/10.32523/ejpfm.2021050207